STRENGTHENING DIGITAL MARKETING SUPPORTED BY THE WEB PROFILE OF MSMES KROKET KERATON BU CHRISTINA WORO SURYATI COLOMADU - Retnoningrum; Resihono , Legowo Dwi; Sarjana Rini, Luluk Takari; Hutami , Sri; Sri Rahayu, Bakti; Mustaqomah, Erniyawati; Harjono (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program focuses on enhancing digital marketing capabilities for the Kroket Keraton MSMEs in Tohudan Village, Colomadu, Central Java. Kroket Keraton MSMEs, which have traditionally relied on conventional sales, have faced challenges in reaching a wider market and increasing sales. Through this program, intensive training and mentoring on digital marketing strategies were provided, including the use of social media, creating engaging content, search engine optimisation (SEO), and digital ad management. The results of this program showed a significant increase in the digital marketing knowledge and skills of MSME actors, as well as an increase in sales and market reach. Additionally, this program helped build brand awareness and customer loyalty through more effective and efficient digital marketing approaches. Thus, this community service program is expected to serve as a model for empowering other MSMEs in facing the challenges of the digital era.